2019
DOI: 10.1055/a-0942-1875
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dietary Supplements in Depression and Anxiety – A Narrative Review

Abstract: Introduction Dietary supplements are very widely used in the general population and there is a growing market for them, which is against the recommendations of the German Society for Nutrition. There is some evidence that dietary supplements are useful additions in the treatment of psychiatric disorders. This review is an overview of available practical knowledge regarding the use of supplements in psychiatric treatment. In particular, the review focused on the diagnosis of depression and anxiety in terms of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
1
14
0
1
Order By: Relevance
“…Although immobility time was comparably greater in vehicle treated acute stressed group but appeared insignificant. Previous studies have stated that Vit D2 supplementation amends depression and anxiety like symptoms ( Hoffmann et al, 2019 ). Clinical trial of depressed older (aged 60 years) patients with Vit D2 supplementation indicates its antidepressant potential (Alvin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although immobility time was comparably greater in vehicle treated acute stressed group but appeared insignificant. Previous studies have stated that Vit D2 supplementation amends depression and anxiety like symptoms ( Hoffmann et al, 2019 ). Clinical trial of depressed older (aged 60 years) patients with Vit D2 supplementation indicates its antidepressant potential (Alvin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent RCT, supplementation with 1200 IU/day vitamin D for 12 months had no effect on depressive symptoms and physical functioning in older persons with relatively low vitamin D status, clinically relevant depressive symptoms, and poor physical functioning [27]. Similarly, another recent review indicated contradictory information between vitamin D for treatment of depressive symptoms [28]. Similarly, although human studies strongly support a correlation between low levels of circulating 25-hydroxyvitamin D (25(OH)D) and cognitive impairment or dementia in aging populations, prior clinical interventional studies have failed to associate increased 25(OH)D levels with improved cognitive outcomes.…”
Section: Vitaminsmentioning
confidence: 99%
“…For example, Kazemi et al 17 explained that dietary supplementation, such as prebiotic use, significantly decreased the Beck Depression Inventory (BDI) scores compared with the placebo group, after eight weeks of intervention. Other dietary supplementations, such as polyunsaturated fatty acid (PUFA), vitamin D, 18 B12, 19 magnesium, zinc, 20 and curcumin, 21 have also been studied for their efficacy and effects as add-on supplements for depression treatment. In a review conducted by Hoffman et al, 18 vitamin D and PUFA supplementation had complementarily positive effects on depressive symptoms, anxiety, and pain.…”
Section: Introductionmentioning
confidence: 99%